2011
DOI: 10.1002/eji.201141490
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of yeast nucleic acids triggers a host‐protective type I interferon response

Abstract: Although type I interferons (IFN-a/b) have been traditionally associated with antiviral responses, their importance in host defense against bacterial pathogens is being increasingly appreciated. Little is known, however, about the occurrence and functional role of IFN-a/b production in response to pathogenic yeasts. Here, we found that conventional DCs, but not macrophages nor plasmacytoid DCs, mounted IFN-b responses after in vitro stimulation with Candida spp. or Saccharomyces cerevisiae. These responses abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
81
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(86 citation statements)
references
References 36 publications
5
81
0
Order By: Relevance
“…126 TLR7 is required for the recognition of single-stranded RNA from C. albicans and the mice lacking TLR7 were hypersusceptible to systemic C. albicans infection. 26,27 Of note, inflammasome plays an important role in antifungal immune response. Inflammasome is a cytoplasmic proteolytic multimeric protein complex expressed in myeloid cells, and consists of NLRs and several adaptors.…”
Section: Prrs Of Neutrophils and Monocytes/macrophagesmentioning
confidence: 99%
See 1 more Smart Citation
“…126 TLR7 is required for the recognition of single-stranded RNA from C. albicans and the mice lacking TLR7 were hypersusceptible to systemic C. albicans infection. 26,27 Of note, inflammasome plays an important role in antifungal immune response. Inflammasome is a cytoplasmic proteolytic multimeric protein complex expressed in myeloid cells, and consists of NLRs and several adaptors.…”
Section: Prrs Of Neutrophils and Monocytes/macrophagesmentioning
confidence: 99%
“…TLR7 is required for the recognition of single-stranded RNA of C. albicans. 26,27 Of note, some CLRs are involved in the recognition of C. albicans, including Dectin-1, Dectin-2, Dectin-3 (originally named murine macrophage C-type lectin, MCL), the dendritic cell-specific ICAM3-grabbing non-integrin (DC-SIGN), the macrophage mannose receptor (MR), Galectin-3, and the macrophage-inducible C-type lectin (Mincle). 28,29 Dectin-1 recognizes b-(1,3)-glucan, while the rest CLRs recognize different mannose-relative structures.…”
mentioning
confidence: 99%
“…These studies demonstrated that type I IFN induces severe kidney damage by promoting excessive recruitment and activation of inflammatory monocytes and neutrophils. However, other reports suggest that type I IFN can be beneficial as part of the host immune response to C. albicans (28,31). Other studies related to sepsis show that type I IFN plays a critical role in promoting lethal endotoxemia (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…Unmethylated CpG motifs in A. fumigatus DNA stimulate mouse bone marrow-derived DCs (BMDCs) and human pDCs to secrete inflammatory cytokines in a TLR9-dependent manner [132], contributing to the establishment of anti-fungi immune response states. In addition to A. fumigatus, Candida albicans, S. cerevisiae, Malassezia furfur, and Cryptococcus neoformans DNAs are capable of triggering TLR9 recruitment, demonstrating that TLR9 is compartmentalized selectively to fungal phagosomes and negatively modulates macrophage antifungal effector functions [108,109,133]. Interestingly, hemozoin, a crystalline metabolite of hemoglobin produced by Plasmodium falciparum, acts as an inducer of TLR9 and potently activates macrophages and DCs to produce inflammatory cytokines and chemokines [130].…”
Section: /2mentioning
confidence: 99%
“…Recent studies also showed that IFN-a/b is induced by Candida spp. and Saccharomyces cerevisiae RNA/DNA by a mechanism that involves endosomal recognition of fungal RNA and DNA by TLR7 and TLR9, respectively, and absolutely requires MyD88 [108,109].…”
Section: /2mentioning
confidence: 99%